An analysis of key factors affecting New Town Planning with a human-centred approach - Izadi, Maliheh; Varesi, Hamidreza; Jafari Vardanjani, Mehdi (Bulletin of Geography. Socio-economic Series, 2021)
Since new towns are to meet the needs of the metropolitan population, it is required to acquaint the populations with the new scientific-technical methods and take one more step towards civilisation. Given that the New Town seeks to provide the latest facilities for citizens, a human-oriented approach can be proposed. New Urbanism with a humanistic approach requires coherent and dynamic planning. New structures and the various needs of the New Towns require comprehensive and integrated planning to utilise recent facilities to lead New Towns toward a human-centred attitude. Therefore, the main purpose of this study is to analyse the key factors affecting the planning of New Towns with a humanistic approach. The method in this research is a descriptive-analytical survey. In the first step of the research, a list of primary factors involved in planning new cities was identified as research variables, using documentary sources and previous research. Then the research variables were analysed based on the Delphi method. Accordingly, 34 variables were provided in five domains for 50 experts in urban planning issues in the form of questionnaires to be analysed in matrices. The findings of the study are demonstrated in five aspects: cultural-social, physicalspatial, economic, environmental, and governance topics, with 34 components. The results show that citizenship rights, social capital, transparency, accountability, law, participation, consensus, quality of performance and managerial effectiveness, efficiency, economic welfare, sustainable active economy, meeting economic needs, quality of texture, and spirituality have the highest impact and the lowest affectedness on the realisation of human-centred New Urbanism. The results can be useful and effective by establishing integrity and fundamental theoretical principles in planning, implementation and strategic control of New Towns.